DEVELOPMENT OF A TELEMETRIC TEMPERATURE MONITORING SYSTEM FOR BOVINE APPLICATION - ARCE, ALDO IVAN CÉSPEDES; SILVA, ANA CAROLINA DE SOUSA; TECH, ADRIANO ROGÉRIO BRUNO; COSTA, ERNANE JOSÉ XAVIER (Revista Brasileira de Engenharia de Biossistemas, 2007)
This paper presents a complete telemetric temperature monitoring system developed to speed upbovine behavior studies under temperature exposure. The equipment uses wireless sensortechnology and is interfaced by a computer program. The sensor can be implanted into animal.Results obtained show that the developed system is able to monitor bovine temperatures with asample rate of five minutes during 30 days with accuracy of 0.0625o C.